Cytochrome b Mutations F129L and G143A Confer Resistance to Azoxystrobin in Cercospora nicotianae, the Frogeye Leaf Spot Pathogen of Tobacco - Dixon, Edward (Plant disease, 2020)
Azoxystrobin is the only synthetic, systemic fungicide labeled in the United States for management of frogeye leaf spot (FLS) of tobacco (Nicotiana tabacum L.), caused by Cercospora nicotianae. Though traditionally considered a minor disease in the United States, FLS has recently become yield and quality limiting. In 2016 and 2017, 100 C. nicotianae isolates were collected from symptomatic tobacco from eight counties in Kentucky, United States. Prior to azoxystrobin sensitivity testing, some C. nicotianae isolates were found to utilize the alternative oxidase pathway and, after assay comparisons, conidial germination was utilized to evaluate sensitivity in C. nicotianae as opposed to mycelial growth. Azoxystrobin sensitivity was determined by establishing the effective concentration to inhibit 50% conidial germination (EC50) for 47 (in 2016) and 53 (in 2017) C. nicotianae isolates. Distributions of C. nicotianae EC50 values indicated three qualitative levels of sensitivity to azoxystrobin. Partial cytochrome b sequence, encompassing the F129L and G143A mutation sites, indicated single-nucleotide polymorphisms (SNPs) conferring the F129L mutation in C. nicotianae of moderate resistance (azoxystrobin at 0.177 ≤ EC50 ≤ 0.535 µg/ml) and the G143A mutation in isolates with an azoxystrobin-resistant phenotype (azoxystrobin EC50 > 1.15 µg/ml). Higher frequencies of resistant isolates were identified from greenhouse transplant (4 of 17) and conventionally produced (58 of 62) tobacco samples, as compared with field-grown tobacco (<4 weeks prior to harvest; 4 of 62) or organically produced samples (1 of 7), respectively. Together, these results suggest that resistance to azoxystrobin in C. nicotianae occurs broadly in Kentucky, and generate new hypotheses about selection pressure affecting resistance mutation frequencies